Efektivitas Terapi Hipnosis Lima Jari Berbasis Website terhadap Tingkat Kecemasan Pasien Preoperasi Bronkoskopi di RSUP Persahabatan - Salman Al Farisi; Nur Fajariyah; Nita Sukamti; Satinah Satinah (Universitas Malahayati Lampung, 2024)
ABSTRACT This study is based on the high level of anxiety experienced by preoperative bronchoscopy patients. In 2023, at RSUP Persahabatan, approximately 72% of patients experienced anxiety before undergoing bronchoscopy. Preoperative anxiety can affect the success of the procedure, cause discomfort during the operation, and interfere with the patient's recovery post-surgery. Preoperative anxiety can be managed through various methods, such as deep breathing relaxation techniques, music therapy, aromatherapy, hypnotherapy, and distraction techniques. The five-finger hypnosis therapy delivered through a website is considered a potential non-pharmacological intervention to reduce this anxiety. This study aims to evaluate the effectiveness of the five-finger hypnosis therapy delivered through a website in reducing the anxiety levels of preoperative bronchoscopy patients at RSUP Persahabatan. The research method used is quasi-experimental with a pretest-posttest one-group design. The study involved 30 patients (aged 20-50 years) who were scheduled to undergo bronchoscopy and were selected using purposive sampling. The intervention consisted of five-finger hypnosis therapy delivered through a website by the researcher. The results showed that before the five-finger hypnosis therapy, the average anxiety score was 13.00, with 60% of patients experiencing moderate anxiety. After the therapy, the anxiety level decreased to an average of 10.17, with the percentage of patients experiencing no anxiety increasing to 16.7%. The results of the Paired Sample T-Test showed a p-value of 0.001 (p0.005), indicating a significant effect of the five-finger hypnosis therapy delivered through a website on reducing the anxiety levels of preoperative bronchoscopy patients. The conclusion of this study is that the five-finger hypnosis therapy delivered through a website is effective in reducing the anxiety levels of preoperative bronchoscopy patients. This study provides benefits for the development of non-pharmacological interventions in managing preoperative anxiety, particularly in the use of web-based technology to enhance the quality of healthcare services. Keywords: Bronchoscopy, Five-Finger Hypnosis, Non-Pharmacological Intervention, Preoperative Anxiety, Website ABSTRAK Penelitian ini didasarkan pada tingginya tingkat kecemasan yang dialami oleh pasien preoperasi bronkoskopi, pada tahun 2023 di RSUP Persahabatan sekitar 72% mengalami kecemasan saat akan menghadapi operasi bronkoskopi. Kecemasan yang dialami pasien sebelum operasi dapat mempengaruhi keberhasilan prosedur, ketidaknyamanan selama tindakan, dan mengganggu pemulihan pasien setelah operasi. Kecemasan pasien preoperasi dapat diatasi dengan beberapa cara, seperti menggunakan teknik relaksasi napas dalam, terapi musik, aromaterapi, hipnoterapi, dan distraction techniques. Terapi hipnosis lima jari berbasis website dipandang sebagai salah satu intervensi nonfarmakologis yang potensial untuk mengurangi kecemasan tersebut. Penelitian ini bertujuan untuk mengevaluasi efektivitas terapi hipnosis lima jari berbasis website dalam menurunkan tingkat kecemasan pasien preoperasi bronkoskopi di RSUP Persahabatan. Metode penelitian yang digunakan adalah quasi-experimental dengan pretest-posttest one group design. Responden penelitian 30 pasien (20-50 tahun) yang akan menjalani bronkoskopi dan dipilih melalui teknik purposive sampling. Intervensi berupa terapi hipnosis lima jari berbasis website yang diberikan oleh peneliti. Hasil penelitian menunjukkan bahwa sebelum terapi hipnosis lima jari berbasis website menunjukkan skor kecemasan rata-rata 13,00 dengan mayoritas mengalami cemas sedang sebesar 60%. Setelah hipnosis lima jari berbasis website tingkat kecemasan menurun menjadi rata-rata 10,17 dengan peningkatan jumlah pasien yang tidak cemas menjadi 16,7%. Hasil Uji Paired Sample T Test menunjukkan nilai p-value sebesar 0,001 (p0,005) menandakan ada pengaruh signifikan dari terapi hipnosis lima jari berbasis website terhadap penurunan tingkat kecemasan pasien preoperasi bronkoskopi. Kesimpulan dari penelitian ini adalah terapi hipnosis lima jari berbasis website efektif dalam menurunkan kecemasan pasien preoperasi bronkoskopi. Penelitian ini memberikan manfaat bagi pengembangan intervensi nonfarmakologis dalam manajemen kecemasan preoperasi, khususnya dalam penggunaan teknologi berbasis website untuk meningkatkan kualitas layanan kesehatan. Kata Kunci: Bronkoskopi, Hipnosis Lima Jari, Intervensi Nonfarmakologis, Kecemasan Preoperasi, Website